2013
DOI: 10.1371/journal.pone.0060171
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Complications and Women's Behavior in Seeking Care from Skilled Providers in North Gondar, Ethiopia

Abstract: BackgroundMaternal complications are morbidities suffered during pregnancy through the postpartum period of 42 days. In Ethiopia, little is known about women's experience of complications and their care-seeking behavior. This study attempted to assess experiences related to obstetric complication and seeking assistance from a skilled provider among women who gave birth in the last 12 months preceding the study.MethodsThis study was a cross-sectional survey of women who gave birth within one year preceding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 20 publications
(22 reference statements)
16
59
0
Order By: Relevance
“…Many studies in Bangladesh and elsewhere have shown socio-economic disparities in care seeking [22] with some studies documenting positive association between improved wealth status and seeking trained maternity care [9, 11, 12, 15]. In our study, women in the highest two wealth quintiles were about two times more likely to seek trained care both for reported antepartum and intrapartum complications [15], which was in agreement with findings of earlier studies conducted in Bangladesh and in other countries [13, 15]. …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Many studies in Bangladesh and elsewhere have shown socio-economic disparities in care seeking [22] with some studies documenting positive association between improved wealth status and seeking trained maternity care [9, 11, 12, 15]. In our study, women in the highest two wealth quintiles were about two times more likely to seek trained care both for reported antepartum and intrapartum complications [15], which was in agreement with findings of earlier studies conducted in Bangladesh and in other countries [13, 15]. …”
Section: Discussionsupporting
confidence: 92%
“…Also, the care-seeking rate in our study was higher compared to findings of a national survey, conducted 10 years earlier in Bangladesh, where one in three women reported receiving care from a qualified provider for their life threatening antepartum complications [11]. However, the care-seeking rate from a trained provider for obstetric complications that we observed was similar to studies conducted in Bangladesh and Ethiopia [13, 21]. The higher use of trained care in our study population compared to other Bangladesh studies might partly be due to time lag between the studies and partly be the impact of a MNH intervention package that we have been implementing in this population for more than a decade.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Most intercurrences can lead to serious complications and the best way to avoid such complications is through an appropriate and qualified health care [8]. Some studies have identified factors and behaviors that can minimize the effects of pregnancy complications, such as increased educational level, ease of access to the health facility, the availability of the transport system, family support, experience of a previous pregnancy, favorable economic conditions and qualified health care [9,10] In fact, one highlights the importance of ensuring those users a qualified prenatal care, since, through that service, health professionals can perform the monitoring of the main pregnancy complications seeking to avoid major complications for mother and child [2].…”
Section: Discussionmentioning
confidence: 99%